Dual-metal hydroxide@oxide heterojunction catalyst constructed via corrosion engineering for large-current oxygen evolution reaction - Li, Zhong (2023)
Current OER electrocatalysts are hardly applicable for industrial use, which demands high current density (≥ 1000 mA cm-2) at low overpotential (≤ 300 mV) with long-term stability (≥ 100 h). Herein self-supported heterojunction catalyst, NiCo-OH@NixFeyO4 on Fe foam (FF), is in situ synthesized using two-step corrosion engineering. It only requires an overpotential 275 mV to drive the current density of 1000 mA cm-2 with good long-term stability. Theoretical calculations reveal that such good performance is attributable to electron transfer from NiCo-OH to NixFeyO4 which weakens the adsorption energy of reaction intermediate (OOH*) to promote the release of O2 and lowers the free energy barriers for the reaction. Furthermore, a water splitting cell with NiCo-OH@NixFeyO4/FF as anode and CoP@FeP/FF as cathode demonstrates its potential for industrial application. The study presents a general strategy for in situ synthesis of heterojunction catalysts on metal foams using controlled corrosion engineering for various catalytic applications.